Fabrication of gentamicin loaded Col-I/HA multilayers modified titanium coatings for prevention of implant infection - Ma, Le; Zong, Jiajia; Xun, Xiaowei; Hu, Xiaoming; Chen, Zejing; Zhang, Quanchao; Peng, Mengxia; Song, Botao; Ao, Haiyong (Frontiers in Chemistry, 2022)
In this study, gentamicin loaded collagen I/hyaluronic acid multilayers modified titanium coating (TC-AA(C/H)6-G) was fabricated via a layer-by-layer (LBL) covalent immobilization method. The drug releasing properties of collagen I/Hyaluronic acid (Col-I/HA) multilayers and the effect of loaded gentamicin on the antibacterial properties and cytocompatibility of modified TC were investigated. The gentamicin release assay indicated that the Col-I/HA multilayers modified TC exhibited agreeable drug-loading amount (537.22 ± 29.66 µg of gentamicin) and controlled-release performance (240 h of sustained release time). TC-AA(C/H)6-G revealed satisfactory antibacterial activity and inhibited the colonization and biofilm formation of S. aureus. Fortunately, the functions of hMSCs on TC-AA(C/H)6-G did not affected by the loaded gentamicin, and TC-AA(C/H)6-G could improve the adhesion, proliferation and osteogenic differentiation of cells, as well as TC-AA(C/H)6. In vivo animal study indicated that TC-AA(C/H)6-G could effectively control intramedullary cavity infection caused by S. aureus and prevent bone destruction.